Analysis Of The Implementation Of The PDCA Performance Management Model At Kimia Farma. - Aquet Miliki; Dinda Ridho Fikri; Muhammad Nursyahdani; Wahyu Prasetya; Satriadi Satriadi (Brilliant International Journal Of Management And Tourism, 2024)
In this era, many organizations are increasingly using the PDCA model to enhance performance management, and one example is Kimia Farma in KM 9 Tanjungpinang. Despite the implementation of the PDCA model, there are still challenges in performance management at Kimia Farma KM 9 Tanjungpinang. The objective of this research is to understand how performance management is implemented at Kimia Farma KM 9 Tanjungpinang. The research method employed is qualitative, utilizing interviews and direct observations with the pharmacy manager and assistant pharmacist at Kimia Farma KM 9 Tanjungpinang. The findings of this research indicate that Kimia Farma has implemented the PDCA model, including monthly planning sessions. Although challenges persist in the implementation, Kimia Farma conducts weekly evaluations and takes corrective actions to enhance performance management.